Manganese-based Prussian blue nanoparticles inhibit tumor proliferation and migration via the MAPK pathway in pancreatic cancer - Tong, Shanshi; Yu, Zhilong; Yin, Fang; Yang, Qilin; Chu, Juhang; Huang, Luyao; Gao, Wenxue; Qian, Mingping (Frontiers in Chemistry, 2022)
Pancreatic cancer (PC) is one of the deadliest gastrointestinal malignancies. Advances in molecular biology and surgery have significantly improved survival rates for other tumors in recent decades, but clinical outcomes for PC remained relatively unchanged. Chemodynamic therapy (CDT) and Photothermal therapy (PTT) represent an efficient and relatively safe cancer treatment modality. Here, we synthesized Mn-doped Prussian blue nanoparticles (MnPB NPs) through a simple and mild method, which have a high loading capacity for drugs and excellent CDT/PTT effect. Cell line experiments in vitro and animal experiments in vivo proved the safety of MnPB NPs. We stimulated the pancreatic cells with MnPB NPs and performed transwell migration assays. The migration of pancreatic cancer cells was reduced companying with the decrease of two classical proteins in metastasis: matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9). Moreover, MnPB NPs induced ferroptosis, which mediated the MAPK pathway and achieved sustained tumor elimination in nude mice. This effective and safe strategy controlled by irradiation represents a promising strategy for pancreatic cancer.